Prophetic Traditions in the Jawi Book Hidayah al- Salikin: An Analysis of Prophetic Traditions Without Known Status - Ahmad, Khadher; Suliaman, Ishak (Jurnal Usuluddin, 2010)
Researching and re-evaluating old Jawi books of Nusantara has now become a necessity. Among the aspects of the research is to re-evaluate the prophetic traditions found in these Jawi books regardless of it not being prophetic manuscripts. This effort is reflected in the form of collecting all the prophetic traditions, retrieving it and then assigning it an appropriate status. This paper will reveal the evaluation work attempted on the prophetic traditions found in the Sufi literature titled Hidayah al-Salikin fi Maslak al-Muttaqin, authored by Sheikh ‘Abd al-Samad al-Falimbani. The book Hidayah al-Salikin contains 183 Prophetic traditions of several status such as sahih (authentic), da’if (weak), da’if jiddan (very weak), mawdu’ (fabricated) and some prophetic traditions with unknown sources or origin. The colorful variety of these traditions becomes the driving motivation for this research. However, in this paper, the focus of the research will be on the evaluation and analysis of prophetic traditions that have no known status or reputation.